Strategi Manajerial Dalam Menghadapi Ketidakpastian Ekonomi : Studi Pada Industri Perbankan - Ahmad Musseng; Daryanti Daryanti; Asriyana Asriyana (Benefit: Journal of Bussiness, Economics, and Finance, 2025)
This research analyzes the managerial strategies of banks in Makassar in facing economic uncertainty with qualitative approach and case study design on five representative banks. The research was conducted in five stages: preparation, data collection through interviews, observation, and documentation study, data analysis using thematic techniques and local economic contextual analysis, and validation of findings through triangulation of sources and methods. The results show that banks in Makassar adopt adaptive strategies, focusing on strengthening internal management (organizational restructuring, human resource development, and technology-based control systems) and external collaboration (partnerships with fintech, research institutions, and educational institutions). Strategic differences between nationalbanks that are more flexible to local markets and multinational banks that excel in integrated systems and structured risk management were also found. The findings result in a contextualized managerial strategy model and practical recommendations for risk management and service innovation in the banking sector.